Morphological, molecular and histopathological identification of Sarcoptes scabieiinfection in a goat herd at Goa, India - SUSITHA RAJKUMAR; M ANANDHI; SHIRISH D NARNAWARE; SOLOMON RAJKUMAR (Indian Journal of Animal Sciences)
Mange is caused by infestation with mites of different genera which significantly impacts the farm economy by affecting growth and weight gain in young animals. This study was aimed to investigate a severe mange outbreak in a goat herd in North Goa District, Goa, and to characterize the causative pathogen. The disease was diagnosed by clinical signs, gross and histopathologic lesions, microscopical detection of mites, and confirmed by PCR and 16s rRNA sequencing, and the genetic characterization of the S. scabiei isolate. The animals showed pruritus, erythema, papule formation, alopecia and scab formation. Lesions were mainly distributed on the head around the eyes, lips, nostrils, ears, face, and neck. The KOH digestion method showed the different developmental stages of S. scabiei. Histopathological changes like acanthosis, micropustule formation around degenerating mite, acantholysis, infiltration of inflammatory cells and presence of parasite stages and eggs in the tunnels in the stratum corneum were observed. Treatment using Ivermectin, Chlorpheniramine maleate, Deltamethrin and oral vitamin supplements led to the complete recovery of the affected animals. The phylogenetic study based on 16s rRNA and ITS genes revealed that the Goan isolate was phylogenetically close to wild animal and livestock isolates from Egypt, Australia, China and Europe. The study provides pertinent information on the S. scabiei prevalence in the goat population in Goa and shows the potential risks of spread of this zoonotic pathogen and emphasizes the need for the development of preventive measures against infestation in animals in the hot humid coastal region.